Improved thermostability of Thermobifida fusca mannanase obtained by error-prone PCR mutagenesis - Yawei Wang; Qiang Xue; Guan Wang; Zhenggang Han; Jiangke Yang; Hairong Xiong (Biotechnology Letters, 2026)

Enhanced net carbon dioxide sink in rice-duckweed system: Evidence from the diurnal flux variation - Weixuan Liu; Ning Gao; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Lili Zhu; Jian Meng; Junzeng Xu (Agriculture, Ecosystems & Environment, 2026)

Optical properties and sources of water-soluble brown carbon in PM2.5 at an island site in the Pearl River Estuary: Assessing continental and marine influences - Yawei Xue; Yuan Gao; Jianbo Ye; Qianyun Zhong; Cheng Zhang; Yee Jun Tham (Atmospheric Pollution Research, 2026)

BRICS cooperation and ecological sustainability: Unveiling the roles of energy transition, technological innovation, and globalization - Jialiang Wu; Xi Xu; Weihao Wang; Jikun Jiang; Yawei Xue; Ling Jiang (Gondwana Research, 2026)

Chloride Loss in Fine Aerosols over the Atmosphere of Pearl River Estuary - Yuan Gao; Jianbo Ye; Lili Ming; Run Lu; Jiayin Sun; Guizhen Fang; Yawei Xue; Yee Jun Tham (Aerosol Science and Engineering, 2026)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Population challenge, economy, energy decarbonization and information and communication technology: insights of ecological footprint and biocapacity in Belt and Road countries - Jialiang Wu; Xi Xu; Weihao Wang; Jikun Jiang; Yawei Xue; Ling Jiang; Zichuan Quan (Environment, Development and Sustainability, 2025)

Soil pH modulates the impact of ammonia-based fertilizers on N-cycling microbial genes in terrestrial ecosystems - Xue Zhou; Yiyun Chen; Yawei Li (European Journal of Soil Biology, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Unveiling the impact of aging on environmental sustainability in China: New insights from the Fourier ARDL approach - Zichuan Quan; Xi Xu; Jikun Jiang; Weihao Wang; Yawei Xue; Ling Jiang (Journal of Environmental Management, 2025)

Ultrasensitive and high selectivity detection of fibrin using Y-shaped DNA-homing peptide doped probe on localized surface plasmon resonance platform - Yawei Chen; Yuanfu Zhang; Xue Zhao; Wenyu Xu; Shuhao Wang (Analytica Chimica Acta, 2025)

Duckweed (Lemna minor L.) as a natural-based solution completely offsets the increase in ammonia volatilization induced by soil drying and wetting cycles in irrigated paddies - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Yixuan Jia; Jian Gao; Qianjing Jiang; Yong He (Science of The Total Environment, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

An improved current retrieval method for ice-edge eddies from multi-sensor remote sensing image sequences - Xue Yang; Jinsong Chong; Yawei Zhao; Wenjia Zhao (International Journal of Remote Sensing, 2024)

Boron promoted Fe3+/peracetic acid process for sulfamethazine degradation: Efficiency, role of boron, and identification of the reactive species - Yanhong Zhang; Guangbing Liu; Yuzhu Xue; Lichun Fu; Yawei Qian; Minhui Hou; Xiang Li; Chen Ling; Ying Zhang; Yuwei Pan (Journal of Environmental Sciences, 2024)

Integrating Software FMEA and STPA to Develop a Bayesian Network-Based Software Risk Model for Autonomous Ships - Xue Yang; Yawei Zhu; Tao Zhou; Sheng Xu; Wenjun Zhang; Xiangyu Zhou; Xiangkun Meng (Journal of Marine Science and Engineering, 2023)
The autonomous shipping industry is increasingly focusing on enhancing the safety and reliability of software-based systems. Conducting a risk assessment is a requirement for demonstrating the safety equivalence of autonomous ships based on such systems to conventional vessels. Traditional risk assessment models, however, primarily focus on hardware failures, often overlooking potential software-related failures and functional inadequacies. This study proposes a framework integrating Software Failure Mode and Effects Analysis (FMEA), System–Theoretic Process Analysis (STPA), and Bayesian Network (BN) for risk identification of autonomous ship software systems. The results of a case study reveal that the framework sufficiently addresses the multifaceted nature of risks related to software in autonomous ships. Based on the findings of this study, we suggest the need for standardization of software architecture development in the autonomous ship industry and highlight the necessity for an enhanced understanding of AI-specific risks and the development of tailored risk assessment methodologies.

Identification of natural and anthropogenic sources and the effects of climatic fluctuations and land use changes on dust emissions variations in the Qinghai-Tibetan Plateau - Heqiang Du; Yawei Fan; Lihui Luo; Jie Liao; Zongxing Li; Xiufan Liu; Xinlei Liu; Xian Xue; Tao Wang (Agricultural and Forest Meteorology, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Synergistic modification of Ni-rich full concentration gradient materials with enhanced thermal stability - Chi Zhang; Tao Li; Bing Xue; Xiangkun Wu; Liyuan Li; Yawei Guo; Lan Zhang (Chemical Engineering Journal, 2023)

Research on Surrounding Rock Control Technology of Gob-Side Entry Retaining by Directional Roof Cutting in a Deep Coal Mine - Haojie Xue; Shibao Shen; Haoran Lu; Renbao Zhao; Peishuai Li; Yawei Zhao; Qibin Jiang; Longjiang Wang; Beizhan Fan; Tao Qin (Geotechnical and Geological Engineering, 2022)

Population susceptibility differences and effects of air pollution on cardiovascular mortality: epidemiological evidence from a time-series study - Mengyao Liu; Xiaoxia Xue; Baosen Zhou; Yawei Zhang; Baijun Sun; Jianping Chen; Xuelian Li (Environmental Science and Pollution Research, 2019)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)